2020
DOI: 10.3727/216929720x15846938924085
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Mexican Cuisine: Heritage Implications for Food Tourism Promotion

Abstract: This article analyzes how UNESCO's intangible human heritage designation has led to traditional Mexican cuisine being turned into a resource for gastronomic tourism, showing how the State has commodified traditional culinary knowledge for the promotion of tourism. This promotion includes an official discourse that has been appropriated by traditional women cooks, who use these promotional events to build new culinary canons. This article enables a discussion of how traditional Mexican cuisine has become part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…As such, this is one of the main contributions of this article. A destination is enriched if its traditional cuisine has a strong presence through traditional restaurants, or if its cuisine is based on local produce, also referred to as zero kilometer food [ 19 ]. In this regard, this research is relevant in highlighting two aspects: first, the relevance of gastronomy due to the implications in terms of visitors repeating and recommending a trip to the destination; second, the implications for the management of the restaurant itself and for the management of the city through the public policies designed by policymakers.…”
Section: Introductionmentioning
confidence: 99%
“…As such, this is one of the main contributions of this article. A destination is enriched if its traditional cuisine has a strong presence through traditional restaurants, or if its cuisine is based on local produce, also referred to as zero kilometer food [ 19 ]. In this regard, this research is relevant in highlighting two aspects: first, the relevance of gastronomy due to the implications in terms of visitors repeating and recommending a trip to the destination; second, the implications for the management of the restaurant itself and for the management of the city through the public policies designed by policymakers.…”
Section: Introductionmentioning
confidence: 99%
“…reviewed the role of women in improving food tourism in Mexico and showed that food tourism resulted in a decrease in the sexual gap in the country and an increased number of job opportunities (Vázquez-Medina & Medina, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The term cuisine refers to certain types of food in food tourism (Dancausa-Millan et al, 2022;Lai et al, 2019). The cuisine is a type of food and gastronomy; food or culinary is tourism (Alonso & Kok, 2020;Kumar, 2021;Vázquez-Medina & Medina, 2020). However, other studies use cuisine as a form of food tourism (Mohanty & Sadual, 2019).…”
Section: Literature Review 21 Food Tourismmentioning
confidence: 99%